The social organisation of the Penan - Needham, R (1953)
This thesis is based in fieldwork carried out in Borneo from May 1951 to May 1952. It describes something of the history and mode of life of the Penan, a nomadic people numbering about 2650, of whom a third have settled and now live in a fashion similar to that of other more familiar Bornean peoples. The nomadic Penan, with whom I am mainly concerned, live in the primary rain forests that densely cover the uplands and the rocky ridges of the interior. They wander in small groups of from thirty to forty individuals on the average, the extreme of which are separated on the map by about 140 miles of some of the worst country in southeast Asia. It is a harsh land and an exacting one; a land continually drenched with torrential rains throughout the year, folded into great ranges and broken hills and swamps, cut by fast muddy rivers and rocky streams. there is little in it to please a European who lives close enough to it to see it for what it is. The quality of a report depends much on the way the ethnographer sets about his work, and the reception given to what he presents as facts about a strange people depends to some extent on the reader's imaginative realisation (however far short this may fall) of what it costs the observer to obtain them. 'A man must judge his labours by the obstacles he has overcome and the hardships he has endured, and by these standards I am not ashamed of the results.' From introduction; continued in thesis